Effect of GA based PID controller in bidirectional converter - Kumar, S. Satish; Bharathi, K.; Mohan, S. B.; Balakrishnan, T. Suresh; Kumar, J. Anish; Kumar, M. Sasi (Institute of Advanced Engineering and Science, 2024)
The bi-directional direct current to direct current (DC-DC) converter plays a crucial role in applications involving photovoltaic (PV)-based micro grids. These PV-based hybrid systems have become imperative to ensure uninterrupted power supply and meet local power demands. Selecting the right controller for this converter presents a significant challenge. Traditional proportional integral derivative (PID) controllers yield suboptimal efficiency due to their high delay and settling times. This issue can be overcome by implementing a PID controller based on genetic algorithms (GA). An interconnected grid system is employed to regulate the DC connection voltage across various load conditions, with PV serving as the means to sustain electricity generation. Numerous operational modes tailored to demand are explored, and control techniques are used to maintain the desired DC link voltage level, ultimately enhancing the efficiency of both the PV system and the bidirectional converter in on-grid configurations.